COLLOIDAL BISMUTH SUBCITRATE TREATMENT IN COMBINATION WITH SODIUM IODIDE FOR HELICOBACTER PYLORI ERADICATION - A. K. GÜRBÜZ; K. DAĞALP; M. GÜLŞEN; N. KARAEREN; A. ALPER (Turkish Journal of Gastroenterology, 2020)
-